Patterning Bubbles by the Stick-Slip Motion of the Advancing Triple Phase Line on Nanostructures - Zhou, Haihua (Langmuir : the ACS journal of surfaces and colloids, 2018)
The stick-slip motion of the triple phase contact line (TCL) has wide applications in inkjet printing, surface coatings, functional material assembly, and device fabrication. Here, for the first time, we report that on an alumina substrate with nanostructures, the stick-slip motion of the advancing TCL during spreading of an emulsion droplet can serve as an effective nanopatterning process. Air enclosed in the substrate nanostructures can be exchanged with liquid during the "stick" phase, resulting in the formation of bubbles arranged in a ring pattern. The process takes place in two stages: rings of air form first and then, as the volume of air increases, they separate into air bubbles as a result of the Plateau Rayleigh instability. During the first stage, the rings form due to the stick-slip of the advancing TCL and are ascribed to hydrogen-bonding interactions. Ultimate bubble size is dependent on the substrate pore dimensions. The process was simulated using finite-element analysis to elucidate the mechanism associated with subsequent bubble formation. The simulations corroborate well with the experimental results. This stick-slip motion of the advancing TCL provides new insights into the phenomena associated with droplet spreading and wetting, and the ability to control the formation of patterned bubbles will be promising in applications ranging from microfluidics to printing of functional materials and devices based on bubble templates and applications requiring submerged hydrophobic surface